Expert System For Career Early Determination Based On Howard Gardner's Multiple Intelligence - Rizky Ema Wulansari; RH Sakti; Ambiyar Ambiyar; M. Giatman; N. Syah; W. Wakhinuddin (Journal of Applied Engineering and Technological Science (JAETS), 2022)
The problem that exists is how to design a tool to help students recognize their potential and abilities so that they can recognize the right potential in higher education based on their potential and abilities, with the influence of technological changes that have penetrated into life and even the world of education, then the purpose of this research is to develop software in the form of an expert system as a technology that can be used by students to be able to recognize their potential. The development of this expert system uses the Software Development Life Cycle (SDLC) method, the design of an expert system to determine the potential in higher education based on Multiple Intelligence. This expert system is designed using the Unified Modeling Language (UML).